Apostasy in Islam: Historical and Legal Perspectives1 - Ocktoberrinsyah, Ocktoberrinsyah (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
This paper starts from the contradiction between the concept of religious freedom in the Qur'an and the concept of apostasy (riddah) in classical Islamic jurisprudence. Some jurists believe that the concept of religious freedom has been reduced to a sectarian and discriminative concept, while riddah itself has undergone a shift in its meaning because of the hasty and out-of-context interpretation. Many jurists have established death penalties for every apostasy regardless some limitations on the concept of riddah. This paper presents some Islamic jurist views on riddah, especially in the classical jurisprudence, and also traces back the historical context of riddah in the past in order to understand the reasons for the rise of the death penalty for apostasy.